Heart toxicity from breast cancer radiotherapy: Current findings, assessment, and prevention - Piroth, Marc D.; Baumann, René; Budach, Wilfried; Dunst, Jürgen; Feyer, Petra; Fietkau, Rainer; Haase, Wulf; Harms, Wolfgang; Hehr, Thomas; Krug, David; Röser, Arnd; Sedlmayer, Felix; et al. (Strahlentherapie und Onkologie, 2019)
Background Late cardiac toxicities caused by (particularly left-sided) breast radiotherapy (RT) are now recognized as rare but relevant sequelae, which has prompted research on risk structure identification and definition of threshold doses to heart subvolumes. The aim of the present review was to critically discuss the clinical evidence on late cardiac reactions based on dose-dependent outcome reports for mean heart doses as well as doses to cardiac substructures. Methods A literature review was performed to examine clinical evidence on radiation-induced heart toxicities. Mean heart doses and doses to cardiac substructures were focused upon based on dose-dependent outcome reports. Furthermore, an overview of radiation techniques for heart protection is given and non-radiotherapeutic aspects of cardiotoxicity in the multimodal setting of breast cancer treatment are discussed. Results Based on available findings, the DEGRO breast cancer expert panel recommends the following constraints: mean heart dose <2.5 Gy; D mean LV (mean dose left ventricle) < 3 Gy; V5 LV (volume of LV receiving ≥5 Gy) < 17%; V23 LV (volume of LV receiving ≥23 Gy) < 5%; D mean LAD (mean dose left descending artery) < 10 Gy; V30 LAD (volume of LAD receiving ≥30 Gy) < 2%; V40 LAD (volume of LAD receiving ≥40 Gy) < 1%. Conclusion In addition to mean heart dose, breast cancer RT treatment planning should also include constraints for cardiac subvolumes such as LV and LAD. The given constraints serve as a clinicians’ aid for ensuring adequate heart protection. The individual decision between sufficient protection of cardiac structures versus optimal target volume coverage remains in the physician’s hand. The risk of breast cancer-specific mortality and a patient’s cardiac risk factors must be individually weighed up against the risk of radiation-induced cardiotoxicity.